Neurophysiological mechanisms and features of autonomic support of productive cognitive activity of intuitive type in young adults - Т. O. Tretyak; І. M. Коfan; О. M. Znanetska; F. F. Boyechko; О. V. Severynovska (Regulatory Mechanisms in Biosystems, 2021)
Is intuition a conscious or subconscious process, a “sixth sense” or a product of learning? This article contains an answer to this question which is based on the disclosure of neurophysiological mechanisms of one of the least understandable types of human cognitive activity. For the first time with the use of cerebral cortex electrical activity mapping, a comprehensive study of the organization of cortical neural networks and the functional state of the autonomic nervous system of female biology students engaged in intuitive thinking has been conducted. The productivity of intuitive thinking is associated with increasing the spectral power of beta2-, delta-, theta-components of the electroencephalogram. The synchronization of the activity of most frequency bands is manifested in the frontal and motor areas of the cortex, which have close connections with the basal ganglia, which are responsible for the formation of skills. In the beta1-band there are probable intrahemispheric long coherences between the anterior and posterior parts of the right hemisphere, at the frequency of beta1,2- and theta-bands of the electroencephalogram they are combined into large cellular ensembles that cover the central-parietal-temporal loci of the cortex. Synchronization of biopotentials in the delta range covers large areas of the cerebral cortex. It has been established that in intuitive thinking the female students with a low standard of efficiency had a high level of central rhythm regulation, and the female students with a high standard of efficiency had a high level of autonomous regulation. Higher performance under intuitive thinking negatively correlated with low frequency findings and positively correlated with high frequency and the value of the square root of the mean squares of the intervals between heartbeats (rMSSD) in the structure of cardiorhythm. Correlation analysis found that productive mental activity is conditioned by the specific integration of cortico-visceral processes: productive intuitive thinking is associated with the activation of autonomic regulation of heart rate variability and coherence in the evolutionarily older delta and delta-theta systems of the brain. Thus, intuition is a scientific set of skills and knowledge, and the topographic signs of synchronization of electrical processes of the cerebral cortex can serve as objective criteria for successful intuitive thinking, which allow one to predict both individual abilities and the state that contributes to their realization.